2015
DOI: 10.1371/journal.pcbi.1004367
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Spatiotemporal Patterns by Biological Variability: General Principles and Applications to Dictyostelium discoideum

Abstract: Spatiotemporal patterns often emerge from local interactions in a self-organizing fashion. In biology, the resulting patterns are also subject to the influence of the systematic differences between the system’s constituents (biological variability). This regulation of spatiotemporal patterns by biological variability is the topic of our review. We discuss several examples of correlations between cell properties and the self-organized spatiotemporal patterns, together with their relevance for biology. Our guidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 116 publications
(175 reference statements)
1
24
0
Order By: Relevance
“…By employing perfusion and live cell imaging of cytosolic cAMP, it has been demonstrated that the onset of collective pulses of cAMP is dictated by the stochastic cAMP pulses that are self-enhanced in the population [ 18 20 ] and that the oscillations require removal of extracellular cAMP by secreted phosphodiesterase [ 21 ]. These studies are largely compatible with a view that oscillations and waves of cAMP can be understood in the framework of reaction–diffusion systems [ 22 ] akin to the well-studied Belousov–Zhabotinsky reaction [ 23 ].…”
Section: Introductionsupporting
confidence: 76%
“…By employing perfusion and live cell imaging of cytosolic cAMP, it has been demonstrated that the onset of collective pulses of cAMP is dictated by the stochastic cAMP pulses that are self-enhanced in the population [ 18 20 ] and that the oscillations require removal of extracellular cAMP by secreted phosphodiesterase [ 21 ]. These studies are largely compatible with a view that oscillations and waves of cAMP can be understood in the framework of reaction–diffusion systems [ 22 ] akin to the well-studied Belousov–Zhabotinsky reaction [ 23 ].…”
Section: Introductionsupporting
confidence: 76%
“…An example is strong and non-monotonous dependence of the density of spiral waves (which regulates the size of the later-stage multicellular aggregates) on the intracellular feedback loop regulating the production of the main signalling substance, cAMP (Sawai et al, 2005 ). Understanding the relationship of regulatory mechanisms and emergent, collective behaviours is an important future challenge in Systems Biology (Grace and Hütt, 2015 ).…”
Section: Disciplinary Perspectivesmentioning
confidence: 99%
“…On the other hand, oscillatory models require some sort of inhomogeneity to be added to the system to produce stable centers and avoid bulk oscillations. It has been shown that increasing the cell parameters along a developmental path or adding random firing decides the location of the observed patterns in an artificial way 2528 which contrast with experimental observations showing that oscillation is a collective effect instead of the work of some specialized cells, where even the cells composing the oscillating center move continuously in and out of the signaling center 29,30 . We suggest that a more simple mechanism is also in play to produce centers for densities less than a mono-layer: the inhomogeneous cell distribution in the system is enough to create stable emitting centers.…”
Section: Discussionmentioning
confidence: 84%